FPGA Implementation of Park-Miller Algorithm to Generate Sequence of 32-Bit Pseudo Random Key for Encryption and Decryption of Plain Text - Bharatesh N; Rohith S (Institute of Advanced Engineering and Science, 2013)
There are many problems arises in randomized algorithms whose solutions are fundamentally based on assumptions that pure random numbers exist, so pseudo-random number generators can imitate randomness sufficiently well for most applications. The proposed scheme is a FPGA implementation of Park-Miller Algorithm for generating sequence of Pseudo-Random keys. The properties like High speed, low power and flexibility of designed PRNG(Pseudo Random Number Generator) makes any digital circuit faster and smaller. The algorithm uses a PRNG Module, it contains 32-bit Booth Multiplier, 32-bit Floating point divider and a FSM module. After generating a sequence of 32-bit Pseudo-Random numbers we have used these numbers as a key to Encrypt 128-bit plain text to become a cipher text and by using the same key to decrypt the encrypted data to get original Plain text. The Programming is done in Verilog-HDL, successfully synthesized and implemented in XILINX Spartan 3E FPGA kit.